Case Report: A case of Fraser syndrome 2 in a Chinese fetus caused by novel compound heterozygous variants in the FREM2 gene - Wei, Weidong; Fan, Yinan; Song, Jiaqi; Lou, Yedan; Zhang, Tao; Yuan, Hua; Jin, Jieyuan; Zhang, Sinan; Jin, Xin (Frontiers in Medicine, 2025)
BackgroundFraser syndrome (FS) is an autosomal recessive inherited malformation disorder characterized by cryptophthalmos, syndactyly, and abnormalities of the respiratory and urogenital tracts. Variants in the FRAS1-related extracellular matrix 2 (FREM2) gene are the major genetic cause. However, clinical diagnosis remains challenging due to phenotypic heterogeneity.MethodsA 24-week pregnant woman came to our hospital for genetic diagnosis. Ultrasound examination showed bilateral renal agenesis or dysplasia, absence of the bladder, and almost oligohydramnios. Trio whole-exome sequencing (Trio-WES) identified two novel compound heterozygous variants in the fetal FREM2 gene: a maternal, frameshift variant, c.5908_5909del, p.Leu1970ValfsTer33, and a paternal, nonsense variant, c.7881C>G,p.Tyr2627Ter.ConclusionWe report a rare case of Fraser syndrome 2 caused by compound heterozygous mutations in the FREM2 gene. Our findings expanded the FREM2 genotypic spectrum and demonstrated the significance of Trio-WES in the prenatal diagnosis of recessive disorders.